Implementasi Model PBL Melalui Pendekatan Saintifik Dalam Meningkatkan Hasil Belajar - Yotam Kasene (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the world of education, the development and introduction of the natural environment is indispensable. Because through natural education humans can recognize and observe the processes that occur in nature. The introduction of nature in elementary schools is taught through learning by studying Natural Sciences (IPA). According to Sitiatava (2012: 51) in Syafriana (2017) "Science is knowledge that studies, explains, and investigates natural phenomena with all their empirical aspects". Science learning has a relationship with the PBL learning model. This learning model trains and develops the ability to solve problems that are oriented to authentic problems and students' actual lives, to stimulate higher-order thinking skills (Sagapa, 2011) in (Rahayu, 2019:33). This is in line with the opinion of Zainsyah et al. (1984: 16) in Akbar (2016: 80), that teachers are still not willing to try to implement a new learning model because they have to change habits that have been practiced for a long time at school. The PBL learning model is very relevant to the learning process developed with a scientific approach, namely an approach that emphasizes more on how students think. The method used is descriptive qualitative, namely research that describes an object, phenomenon that is collected at a research location to support a subject. According to Meleong (2011) (in Anggito, 2018: 14) to improve students' critical thinking is to apply the PBL model. So that students always practice to think critically in solving a problem related to the material taught by the teacher in class